2015
DOI: 10.1016/s1995-7645(14)60334-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic analysis of ferulic acid-puerarin-astragaloside in combination with neuroprotective in cerebral ischemia/reperfusion injury in rats

Abstract: The pharmacokinetics of FA-Pr-Al in combination were closely related its pharmacodynamics in treating ischemia/reperfusion injury, and the components of FA-Pr-Al may have a synergistic pharmacological effect. Astragaloside may play a more pronounced role in regulating IL-1βand NPY levels compared with puerarin or FA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
3
1
Order By: Relevance
“…The total body clearance of ferulic acid was observed to be 17.1 ± 1.59 L/h/kg, following oral administration (150 mg/kg) of ethyl ferulate in rats. In contrast to our observations, lower values of clearance were reported by Ge et al (2015) (0.0004 L/h/kg), Shin et al (2016) (3.27 ± 1.97 L/h/kg at 2 mg/kg and 2.17 ± 4.01 L/h/kg at 10 mg/kg) and Cheng et al (2012a), following oral administration of ferulic acid puerarin astragaloside combination (250 mg/kg), intravenous administration of ferulic acid in rats and oral administration of P. oleracea extract in rats, respectively. The MRT value calculated, following oral administration of ferulic acid in present study was 0.40 h. In accordance with present study, Shin et al (2016) also observed similar MRT values (0.067 h at 2 mg/kg and 0.10 h at 10 mg/kg), following intravenous administration of ferulic acid in rats.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The total body clearance of ferulic acid was observed to be 17.1 ± 1.59 L/h/kg, following oral administration (150 mg/kg) of ethyl ferulate in rats. In contrast to our observations, lower values of clearance were reported by Ge et al (2015) (0.0004 L/h/kg), Shin et al (2016) (3.27 ± 1.97 L/h/kg at 2 mg/kg and 2.17 ± 4.01 L/h/kg at 10 mg/kg) and Cheng et al (2012a), following oral administration of ferulic acid puerarin astragaloside combination (250 mg/kg), intravenous administration of ferulic acid in rats and oral administration of P. oleracea extract in rats, respectively. The MRT value calculated, following oral administration of ferulic acid in present study was 0.40 h. In accordance with present study, Shin et al (2016) also observed similar MRT values (0.067 h at 2 mg/kg and 0.10 h at 10 mg/kg), following intravenous administration of ferulic acid in rats.…”
Section: Discussioncontrasting
confidence: 99%
“…The elimination half-life (t 1/2β ) of ferulic acid following oral administration of ethyl ferulate in the present study was 0.11 ± 0.01 h. In accordance to present study, Shin et al (2016) observed elimination half-life of 0.08 h at 2 mg/kg and 0.11 h at 10 mg/kg following intravenous administration of ferulic acid in rats and Cheng et al Mean apparent volume of distribution (Vd area ) of ferulic acid following oral administration of ethyl ferulate was 2.85 ± 0.57 L/kg in rats. It is in agreement with value of volume of distribution (12.4 L/kg) observed following oral administration of ferulic acid puerarin astragaloside combination in rats (Ge et al, 2015). Whereas, lower values of volume of distribution were reported by Cheng et al (Qi et al, 2007) and following oral administration of P. oleracea extract in rats, respectively (Cheng et al, 2012a).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The measurements were performed at room temperature. The data thus obtained was analyzed using the LCsolution Version 1.21 software (Ge et al, 2015; Sinha et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…They may exert synergistic effects when used in combination with other chemical drugs. For example, AS-IV and ligustrazine were previously found to antagonize ischemia-reperfusion injury in a rat model of acute cerebral ischemia [ 135 ]. A previous study found that the combined use of atorvastatin and AS-IV could more effectively reduce the inflammatory response in mice than either of the two agents [ 136 ].…”
Section: Discussion and Future Outlookmentioning
confidence: 99%